2006
DOI: 10.1677/joe.1.06685
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin delays hair regrowth in mice

Abstract: Mammalian hair growth is cyclic, with hair-producing follicles alternating between active (anagen) and quiescent (telogen) phases. The timing of hair cycles is advanced in prolactin receptor (PRLR) knockout mice, suggesting that prolactin has a role in regulating follicle cycling. In this study, the relationship between profiles of circulating prolactin and the first post-natal hair growth cycle was examined in female Balb/c mice. Prolactin was found to increase at 3 weeks of age, prior to the onset of anagen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 49 publications
(75 reference statements)
4
46
0
Order By: Relevance
“…Since multiple hormones change during pregnancy and lactation, Stat5 activation in bulge SCs could be due to Prl or another molecular factor. To test whether p-Stat5 activity is downstream from Prl signaling, we reduced systemic Prl levels with bromocriptine (BRC), a dopamine agonist that depletes secretion of pituitary Prl (Craven et al 2006;Larsen and Grattan 2010). We confirmed that treatment of mice with a low dose of BRC during pregnancy diminished serum Prl levels to nonpregnant levels while still permitting successful lactation (Fig.…”
Section: Prl Signaling Is Activated In Follicular Scs During Pregnancymentioning
confidence: 75%
See 3 more Smart Citations
“…Since multiple hormones change during pregnancy and lactation, Stat5 activation in bulge SCs could be due to Prl or another molecular factor. To test whether p-Stat5 activity is downstream from Prl signaling, we reduced systemic Prl levels with bromocriptine (BRC), a dopamine agonist that depletes secretion of pituitary Prl (Craven et al 2006;Larsen and Grattan 2010). We confirmed that treatment of mice with a low dose of BRC during pregnancy diminished serum Prl levels to nonpregnant levels while still permitting successful lactation (Fig.…”
Section: Prl Signaling Is Activated In Follicular Scs During Pregnancymentioning
confidence: 75%
“…2A). This finding was particularly interesting given that Prl signaling has previously been implicated in the regulation of hair growth (Craven et al 2001(Craven et al , 2006Foitzik et al 2003Foitzik et al , 2006). However, a role for Prl signaling in the regulation of bulge SC activity has not been reported.…”
Section: Nfatc1 Promotes Prlr Expression In Bulge Scsmentioning
confidence: 80%
See 2 more Smart Citations
“…Prolactin is implicated in hair growth regulation in both mice and human [112][113][114]. Similarly, melatonin has been reported to promote hair growth in animals and in humans, where topical application of melatonin induced hair, probably through induction of anagen [115].…”
Section: Molecular Control Of Hair Follicle Development and Cyclingmentioning
confidence: 98%